2020
DOI: 10.3389/fmicb.2020.577497
|View full text |Cite
|
Sign up to set email alerts
|

An Educational Bioinformatics Project to Improve Genome Annotation

Abstract: Scientific advancement is hindered without proper genome annotation because biologists lack a complete understanding of cellular protein functions. In bacterial cells, hypothetical proteins (HPs) are open reading frames with unknown functions. HPs result from either an outdated database or insufficient experimental evidence (i.e., indeterminate annotation). While automated annotation reviews help keep genome annotation up to date, often manual reviews are needed to verify proper annotation. Students can provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 91 publications
(120 reference statements)
0
5
0
Order By: Relevance
“…These findings suggested that GAMYB genes could be differently regulated under different stresses, which might result from the expression change of corresponding miRNA159s. Most proteins can be functionally annotated via an experimental and computational approach, but some proteins with unknown domains are referred to as hypothetical proteins [ 46 ]. Dca019932 , one of the predicted Dof-miR159-targeted genes encoding the hypothetical protein, was enriched in terms of DNA-binding transcription factor activity by the GO analysis ( Table S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that GAMYB genes could be differently regulated under different stresses, which might result from the expression change of corresponding miRNA159s. Most proteins can be functionally annotated via an experimental and computational approach, but some proteins with unknown domains are referred to as hypothetical proteins [ 46 ]. Dca019932 , one of the predicted Dof-miR159-targeted genes encoding the hypothetical protein, was enriched in terms of DNA-binding transcription factor activity by the GO analysis ( Table S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in early genome sequencing endeavors, numerous computationally predicted open reading frames (ORFs) encoded proteins lacking functional annotation, called hypothetical proteins (Amatore et al, 2020). An ORF that exhibited sequence homology to enzymes in the Glycoside Hydrolase (GH) family attracted attention.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the promising results obtained in our previous research (Chavez-Fumagalli et al, 2019; Costa et al, 2021), we utilized and modeled MOGS (formerly categorized as a hypothetical protein) as a potential target and receptor in this study to evaluate the effect of NPs (Figure 3A). Notably, in early genome sequencing endeavors, numerous computationally predicted open reading frames (ORFs) encoded proteins lacking functional annotation, called hypothetical proteins (Amatore et al, 2020). An ORF that exhibited sequence homology to enzymes in the Glycoside Hydrolase (GH) family attracted attention.…”
Section: Discussionmentioning
confidence: 99%
“…The FASTA contig data were then aligned using the Basic Local Alignment Search Tool (BLAST) on the NCBI website to compare the nucleotide sequences in Genbank and calculate their statistical match so that the yeast species with the highest identification could be identified. The characteristics of sequences that had high identification had the same maximum score and total score, query coverage up to 100%, e-value of 0.0 (zero), and percentage identify of 100% [51].…”
Section: Isolation and Identification Native Yeast From Tofu Wastewatermentioning
confidence: 96%